Existence and Introduction of Islamic Economics: Role and Relevance - Khan, Bilal Ahmad (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2020)
The collection of rules, values and standards of conduct that organize economic life and establish relations of production in an Islamic society is Islamic economic system. These rules and standards are based on Islamic order recognized in Qurran. Islamic economics based on specific concept of universe and the creation of man is contradictory to the concept adopted and accepted by modern science. Islamic economics postulates although ability and expertise is required for progress and growth but distribution of resources completely dependent on it would be cruel, inhuman and bereft of kindness, and lead to oppression. Islamic economics does not favor making human ability and expertise the fulcrum of resource distribution. It should be kind, considerate and based on justice and fairness. This is because according to Islamic philosophy, ownership is considered to be a trust from Allah which has been bestowed on the rich so that they may utilize it correctly. In Islamic economics the role of the individual, has inclinations and his aims and objectives occupy a central position and are vitally important. He is definitely a rational being but his level of rationality is not confined to the calculations of cost and profit. An individual does not want merely to obtain monetary profit and physical pleasure and leisure but he also wants and aims for something beyond what the material world has to offer. The main aim of the study is to find out the relationship between Islam and economics. In Islamic economics the comprehensive moral training of the individual, his technical and educational ability, his aims and his priorities are of primary importance. According to Islamic economics the means of acquiring wealth has the same importance as wealth itself. Dishonesty, abuse of trust and earning of wealth through fraudulent ways and means may perhaps increase the status of an individual but the society suffers because of it on the whole. This leads to an unjust and oppressive economic system.